Total Factor Productivity Growth, Efficiency and Technological Progress of the Malaysian Manufacturing Sector - Md Isa, Roslina (2005)
Productivity growth has always been an important aspect of Malaysia's economic policy. This is evident in every stage of Malaysia's economic development plans. Sustainable economic growth need to continuously focus on improvements in productivity. Productivity-driven growth has gained momentum in many countries since the 1970's. The Seventh Malaysia Plan (1 995-2000), had placed the importance of productivity with a shift in policy, where productivity-driven strategy was the primary synergy to growth in the future. The productivity-driven strategy is further emphasised in the Eighth Malaysia Plan (2001-2005) and in the Third Outline Perspective Plan (OPP3) (2001-2010). As a result, Malaysia was able to recover from the financial crisis faced in 1997 and experience sustainable economic growth. In view of Malaysia's current full employment situation, total investment is expected to decline. Malaysia's future growth henceforth will depend more on productivitydriven growth strategies. Enhancing productivity growth is essential to achieve high economic growth substantial improvement in income distribution, relative price stability and poverty eradication. Due to limited resources and capacity in capital accumulation accompanied by stiff competition in attracting foreign investments, it has become more pertinent to move the economic development strategy from input-driven to productivity-driven growth by enhancing the contribution of Total Factor Productivity (TFP). As Malaysia moves forward to achieve her goals as set in Vision 2020, she is expected increasing her bottlenecks and limitations especially in terms of skill and organisational/technological capabilities. Shortage of labour will also increase the cost of production which would lead to the erosion of competitiveness. Furthermore, she will increase competitiveness due to globalisation and liberalisation. Nonetheless, that there has been relatively low TFP growth both in the manufacturing sector as well as the economy as a whole. The main objective of this dissertation is to demonstrate the usefulness of recent developments in stochastic frontier analyses in measuring the TFP, efficiency and technological progress in Malaysian manufacturing industries (1985-2001), and the specific objectives are: (i) To provide alternative estimations of technical and cost/allocative efficiency, technological progress and TFP of Malaysian manufacturing sector by using four alternative approaches: Production Function (Cobb Douglas Production Frontier (CDP), Translog Production Frontier (TP)) and Dual Cost Function (Cobb Douglas iii Cost Frontier (CDC) and Translog Cost Frontier (TC)); (ii) To review and identify the underlying impact, assumptions, approach, nature and applications of the above models for Malaysia; (iii) To review the results of alternative estimates of efficiency, technological progress and TFP; (iv) To discuss the relationships between technological progress, efficiency and TFP in Malaysian manufacturing industries; (v) To utilise the results of the models in planning for higher TFP growth; and (vi) To provide some policy implications. According to economists, there are three sources contributing to economic growth of a nation: inflation rate, employment growth and productivity growth. In exploring the later, this study uses 4 alternative models, and the selected final model is the translog cost frontier model. This provides estimations of technical and cost 1 allocative efficiency, technological progress and TFP of twenty selected Malaysian manufacturing sub-sectors using stochastic frontier panel data of time-variant. This study has been able to provide a detailed trend analysis of TFP growth, technological progress, allocativelcost efficiency and the effects of scale economies at 3 and 5-digits sub-sector level of the Malaysian manufacturing sector. The importance of measuring the two components of TFP growth i.e., technicallcost efficiency change and technological progress is that they may provide insights into the causes of low productivity. In this study, the methodologies of stochastic frontier production and cost are employed using microlfirm level data. Microlfirm level data have the advantage of overcoming some of the measurement problems and aggregation bias associated with aggregated industry data. Furthermore, the stochastic frontier production and cost methods will enable us to separate the contributions of technological progress and changes in technicallcost efficiency to TFP growth. The latter can also provide important policy guidelines on the possible factors underlying the productivity issue. This study has provided TFP growth estimates which show considerable effects by changes in technicallallocative efficiency technological progress and scale of components. The overall manufacturing sector for the period 1986-2001 registers TFP growth of 0.69%. The sub-sectors which register high TFP growth are textiles, wood products, other chemicals products, nonferrous metal, electrical machinery, beverages and other manufacturing. Subsectors with low TFP growth are machinery except electrical, rubber products, transport equipment and fabricated metal. The allocativelcost efficiency is the main contributor to TFP growth as compared to technological progress. The overall manufacturing sector for the period 1985-2001 registers an efficiency contribution of 66.0%, scale components 33.0% and technological progress 1 .O% to the TFP. These determinants will give a positive significant effect on productivity growth.